Evaluation of lipase levels in patients with nephropathia epidemica - no evidence for acute pancreatitis - Kitterer, Daniel (BMC Infect Dis, 2015)
BACKGROUND: The most common causative agent for hemorrhagic fever with renal syndrome in Germany is Puumala virus (PUUV) and a high percentage of patients with PUUV infection have gastrointestinal (GI) symptoms. The aim of the present study was to determine the prevalence of increased lipase levels and acute pancreatitis during nephropathia epidemica (NE) in 166 patients from Germany. METHODS: Clinical and laboratory data during the acute phase of the disease were obtained from medical reports and files from 456 patients during acute hantavirus infection. Patients in whom serum lipase levels were determined during acute course of the disease were included in the study. RESULTS: Lipase levels at the time of diagnosis were determined in 166 of the 456 NE patients (36 %). Of the 166 patients, 25 (15 %) had elevated lipase levels at the time of admission to hospital or first contact with general practitioner/nephrologist. In total 7 patients had a threefold increased serum lipase above the normal range. Abdominal pain was not more often present in the group of patients with elevated serum lipase compared to the lipase-negative group (9/25 vs 58/141). Abdominal ultrasound and CT scans revealed no signs of pancreatitis in any of the patients. Patients with elevated serum lipase had higher serum creatinine peak levels (p = 0.03) during the course of the disease. CONCLUSIONS: Elevated lipase levels were common in our patient cohort and might reflect a more severe form of NE. NE does not lead to acute pancreatitis.